Studying justice: measurement, estimation, and analysis of the actual reward and the just reward - Guillermina Jasso (Institute for the Study of Labor (IZA), 2007)
This paper describes procedures for measuring and estimating the fundamental quantities in the study of distributive justice. We examine a variety of methods for measuring the actual reward and the just reward, for both self and other, including direct and indirect methods for measuring the just reward. Finally, we provide an extended illustration of one of the two indirect methods, the one-reward-per-rewardee method, obtaining estimates not only of ideas of the just earnings for others but also of just rates of return to personal characteristics as well as perceived overall injustice and its decomposition into poverty and inequality components
urn:nbn:de:101:1-20080422285
Keywords: 330; Verteilungsgerechtigkeit; Disparitätsmaß; Theorie